2021
DOI: 10.3389/fendo.2021.774686
|View full text |Cite
|
Sign up to set email alerts
|

Early Initiation of Temozolomide Therapy May Improve Response in Aggressive Pituitary Adenomas

Abstract: IntroductionAggressive pituitary adenomas (APAs) are, by definition, resistant to optimal multimodality therapy. The challenge lies in their early recognition and timely management. Temozolomide is increasingly being used in patients with APAs, but evidence supporting a favorable response with early initiation is lacking.MethodsThis was a single-center study of all patients with APAs who received at least 3 cycles of temozolomide (150–200 mg/m2). Their baseline clinico-biochemical and radiological profiles wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The fact that earlier administration of the drug in her case could have yielded better results is plausible. In view of the recent proposition to classify invasive and highly proliferative (Ki67 > 10%) tumors as having malignant potential [ 37 ], our patient could have, in retrospect, been initiated with TMZ earlier without discontinuation of the DA [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that earlier administration of the drug in her case could have yielded better results is plausible. In view of the recent proposition to classify invasive and highly proliferative (Ki67 > 10%) tumors as having malignant potential [ 37 ], our patient could have, in retrospect, been initiated with TMZ earlier without discontinuation of the DA [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…18,88,89 In addition to surgery and radiation therapy, temozolomide is currently the only oral chemotherapeutic drug considered to be effective for pituitary adenomas, and some studies have suggested that early treatment with temozolomide may also have positive effects in patients with functional invasive pituitary adenomas. 17,90 Immunotherapy is a promising treatment that has shown clinical activity in many cancer types. 91,92 Previous studies have explored pituitary adenomas and invasive pituitary adenomas at the molecular level, and have summarized the therapeutic targets and clinical experience.…”
Section: Current S Tatus Of Immunother Apy For Pituitary Adenomamentioning
confidence: 99%
“…Surgical treatment is currently the first choice of treatment for pituitary adenomas and refractory pituitary adenomas; however, the postoperative recurrence rate of some tumors remains high 18,88,89 . In addition to surgery and radiation therapy, temozolomide is currently the only oral chemotherapeutic drug considered to be effective for pituitary adenomas, and some studies have suggested that early treatment with temozolomide may also have positive effects in patients with functional invasive pituitary adenomas 17,90 …”
Section: Current Status Of Immunotherapy For Pituitary Adenomamentioning
confidence: 99%
See 1 more Smart Citation
“…While it appears that the assessment of MGMT status is critical in predicting a therapeutic response in other tumors (e.g., glioblastomas), it is still controversial in pituitary tumors. In a recent cohort study of 35 AgPitNET patients, all TMZ responders had <15% MGMT expression, whereas non-responders had an average of 50% MGMT expression [ 35 ]. A recent meta-analysis study showed that the radiologic response rate was significantly lower in patients with AgPitNET and MetPitNETs with high MGMT expression compared to that obtained in the patients with minimal and intermediate MGMT expression, with no significant difference between the latter two groups [ 32 ].…”
Section: Therapeutic Managementmentioning
confidence: 99%